Pengembangan Usaha Hidroponik 55 dalam Memproduksi Makanan Olahan Sayuran dan Mewujudkan Program Eco-Eduwisata - Fitri Mailani; Eli Ratni; Donny Eros; Jauharry Jauharry; Mulyanti Roberto Muliantino (Warta Pengabdian Andalas, 2021)
Hydroponics 55 is an agricultural business that produces healthy vegetables without pesticides and processed food products. Continuous assistance is essential to increase the productivity of developing companies. The purpose of this activity is to assist partners in growing their business, namely in making processed products of Hydroponics 55 by making "Hydroponic Kitchen 55" and the Eco-Eduwista program in an urban area. This activity was carried out for three months, namely October to December 2021. The activities were guiding the management to have home industry food permits (P-IRT) and business identification numbers (NIB) certificates, developing a "Hydroponic Kitchen 55" business. The team also improved hydroponic vegetable packaging, FGD related to the marketing strategy of Hydroponic 55 vegetables and their processed products. They prepared and built a simple greenhouse in the Hydroponic 55 agricultural area, launched an eco-tourism program and a training centre on hydroponics, and introduced healthy food processed products to visitors. Furthermore, it needs consistency in product quality to compete with other products in the market. Planning for testing the ingredient of hydroponic processed foods also urge to be followed up so that the health benefits of the resulting product are scientifically proven.